العوامل المؤثرة في الاستهلاك الإدماني لدى المرأة الأردنية في مدينة عمان : دراسة ميدانية - القرشي، ظاهر رداد (جمعية إدارة الاعمال العربية, 2012)
هدفت هذه الدراسة إلى قياس وتحديد ظاهرة الاستهلاك الإدماني لدى المرأة الأردنية بالإضافة إلى تحديد العوامل المؤثرة في الاستهلاك الإدماني قام الباحث بأخذ عينة ملائمة مقدارها (1000) امرأة أردنية، تم توزيعها على السيدات اللواتي يقطن في مناطق مختلفة في مدينة عمان الكبرى وضواحيها. اعتمدت الدراسة على المصادر الثانوية للبيانات (الأدبيات، والدراسات السابقة المتعلقة بموضوع الدراسة)، لبناء الإطار النظري للدراسة وصياغة الفرضيات ومقاييسها المستخدمة، توصلت الدراسة بشكل عام إلى أن نسبة الاستهلاك ألإدماني عند المرأة الأردنية في مدينة عمان كانت (26.5%)، حيث أن عدد السيدات المصابات بالاستهلاك ألإدماني (164) سيدة من أصل (٦١٨) سيدة من عينة الدراسة، أوصت الدراسة بضرورة إيجاد وتطوير تشريعات وقوانين وأنظمة حكومية من شأنها كبح الحملات الإعلامية والترويجية المشوهة لمدركات المستهلكين، وبضرورة قيام وزارات الشؤون البلدية والقروية. والصناعة والتجارة، والصحة، وأمانة عمان الكبرى، وجمعيات حقوق الإنسان، وحماية المستهلك، وهيئة الغذاء والدواء، وسلامة البيئة. توصى الدراسة ربات البيوت للقيام بدور القدوة الحسنة والسليمة لأبنائهن. The effecting factors in the addictive Consump¬tion of the Jordanian woman Applied Study Dr. Daher Al- Qurashi This study aimed to measure and quantifies the phe¬nomenon of addictive consumption of the Jordanian women in addition to identifying the factors affect¬ing the Addictive consumption. The researcher takes a suitable sample of (l000)Jordanian women, which distributed to the women who lived in differ¬ent parts of the city of Greater Amman and its sub¬urbs. The study depends on secondary sources of data (literature and previous studies on the subject of the study); to build a theoretical framework for the study and formulation of hypothesis and it's used measures. In general the study found that the proportion of Addictive consumption of the Jordanian women in Amman (26.5%), as the number of women with ad¬dictive consumption (164) woman out of (618)woman of the study sample. Study recommended the need for the creation and development of legislation, laws and government regulations that would restrain the media and pro¬motional campaigns to distorted perceptions of con¬sumers, and the need for the Ministries of Munici¬pal and Rural Affairs, the Ministry of Industry and Commerce, the Ministry Health, the Greater Am¬man Municipality, Human Rights Associations, Consumer Protection Association, the Food and drug Authority, and the Directorate of Environment and Public Safety to work Closely with each other and to address any issue affecting the consumer safety. The study recommends housewives to be a good example for their children, and the study recommends the promoters commitment to the social responsibility towards the consumer ease emotional stimuli as well as to intensify the control over the content of the advertisement and verified before being published by the responsible authorities in order to not mislead the citizen
Keywords: حماية المستهلك -- المرأة الأردنية -- عمان -- الاستهلاك الإدماني -- النظريات الاجتماعية -- الجوانب النفسية -- التسويق -- دخل الفرد -- مستوى المعيشة -- المرأة العاملة